Public Administration and Democracy: The Virtue and Limit of Participatory Democracy as a Democratic Innovation - Karimi, Sirvan (Technium Social Sciences Journal, 2021)
The expansion of public bureaucracy has been one of the most significant developments that has marked societies, particularly Western liberal democratic societies. Growing political apathy, citizen disgruntlement and the ensuing decline in electoral participation reflects the political nature of governance failures. Public bureaucracy, which has historically been saddled with derogatory and pejorative connotations, has encountered fierce assaults from multiple fronts. Out of these sharp criticisms of public bureaucracy that have emanated from both sides of the ideological spectrum, attempts have been made to popularize and advance citizen participation in both policy formulation and policy implementation processes as innovations to democratize public administration. Despite their virtue, empowering connotations and spirit-uplifting messages to the public, these proposed practices of democratic innovations not only have their own shortcomings and are conducive to exacerbating the conditions that they are directed to ameliorate but they also have the potential to undermine the traditional administrative and political accountability mechanisms.